2019
DOI: 10.1186/s13568-019-0830-5
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic cellulolytic bacteria from the gut of the subterranean termite Psammotermes hypostoma Desneux and their role in cellulose digestion

Abstract: The subterranean termite Psammotermes hypostoma Desneux is considered as an important pest that could cause severe damage to buildings, furniture, silos of grain and crops or any material containing cellulose. This species of termites is widespread in Egypt and Africa. The lower termite’s ability to digest cellulose depends on the association of symbiotic organisms gut that digest cellulose (flagellates and bacteria). In this study, 33 different bacterial isolates were obtained from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…However, most of these studies have focused on bacterial and viral communities in ticks [ 18 , 43 , 44 , 45 , 46 , 47 ]. Considering that the arthropod microbiome involves complex interactions among prokaryotes, viruses, and eukaryotic microorganisms [ 6 , 9 , 48 , 49 , 50 , 51 ], the lack of data for eukaryotes may result in incomplete or misleading analyses. The aim of this study was to develop methods for the analysis of eukaryotes in ticks by selectively suppressing the amplification of tick 18S rDNA but allowing the amplification of sequences of other eukaryotes.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of these studies have focused on bacterial and viral communities in ticks [ 18 , 43 , 44 , 45 , 46 , 47 ]. Considering that the arthropod microbiome involves complex interactions among prokaryotes, viruses, and eukaryotic microorganisms [ 6 , 9 , 48 , 49 , 50 , 51 ], the lack of data for eukaryotes may result in incomplete or misleading analyses. The aim of this study was to develop methods for the analysis of eukaryotes in ticks by selectively suppressing the amplification of tick 18S rDNA but allowing the amplification of sequences of other eukaryotes.…”
Section: Discussionmentioning
confidence: 99%
“…In very recent study, L. macrolides and L. fusiformis isolated of from the gut of the subterranean termite Psammotermes hypostoma Desneux are able to digest cellulose [10] and xylan [11]. L. louembei has been isolated from Ntoba Mbodi, an alkaline fermented leaves of cassava from the Republic of the Congo [4].…”
Section: Discussionmentioning
confidence: 99%
“…The function of grooming in termites has always been to replenish their supply of bacteria in the gut, and to remove foreign bodies such as bacteria or parasites from the integument and eliminate through alimentary tracts. However, abnormally high bacterial concentration introduced may cause disruption to their digestive system, by disrupting mutual interactions between termite hosts and their symbionts [ 25 ]. Previous reports showed that grooming increases with the presence of several entomopathogens on the integument of termites [ 26 ].…”
Section: Discussionmentioning
confidence: 99%